Development Of Regional Infrastructure With A Geographic Information System (GIS) Approach For National Food Security - Zefri Zefri (Eduvest - Journal of Universal Studies, 2025)
Geographic Information Systems (GIS) play an important role in regional infrastructure, including Spatial Data Management, Spatial Analysis, Infrastructure Mapping, Supervision and Monitoring, Infrastructure Planning, Risk Reduction, and Efficiency Improvement. The existence of adequate infrastructure in a region has a positive and significant relationship with the food security of that region. The mechanism of this positive relationship can take the form of: increasing accessibility and productivity; improving distribution networks and availability; developing added value from each production output and supporting the independence of communities or regions. The enormous role of GIS in Regional Infrastructure Development is also considered essential in supporting the food security of a region at the national level. The advantage of GIS is its ability to analyze and display data in a spatial context (Geographic Coordinate System), so that it can determine things such as location, conditions, trends, patterns, and modeling. This enables interactive and rapid simulation and spatial analysis of a region.